INOVASI PEMBELAJARAN DIGITAL: PENGARUH MEDIA INTERAKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - khilya (Jurnal Genta Mulia, 2025)
This study discusses the effect of using digital-based interactive learning media on students' mathematical problem-solving skills at the elementary and junior high school education levels in the focus of mathematics subjects. The goal is to find out if the learning media used has an impact on students in improving their mathematical problem-solving skills. The method used in the study is system literature review (SLR). The method is carried out by reviewing articles from google scholar sources from the year of publication 2021 to 2024. The review process consists of 3 stages, namely planning, conducting and reporting, the results and conclusions obtained regarding the use of interactive media for mathematical problem-solving skills have increased from year to year, especially in interactive video media.